An Integrative Review of Enablement in Primary Health Care - Jane Frost; Marian J. Currie; Mary Cruickshank (SAGE Publishing, 2015)
Objectives: To review how enablement is conceptualized and practiced in primary health care and to explore the factors that influence patient enablement in this setting. Method: A narrative integrative literature review was undertaken. Results: Twenty-four articles specifically relating to enablement in primary health care were identified. Three literature reviews, 4 qualitative studies, and 17 quantitative studies were included in the analysis. Conclusions: In the primary health care setting, the concept of enablement is well defined as an outcome measure of quality. The literature exploring the practice of enablement is sparse, but 2 randomized controlled trials suggest enablement is linked to better outcomes for patients with asthma and diabetes. Primary factors influencing enablement included the practitioners' open communication style, the degree to which the practitioner is patient centered, and longer consultations. Other factors found to be associated with enablement were the presenting health issue, general state of health, ethnicity, the patient's own coping strategies and degree of independence, and socioeconomic status. The association between enablement and patients' expectations and satisfaction is less clear. The majority of research on enablement was carried out among general practitioners. Further research into the degree to which patients are enabled by a wider range of health care providers is needed. Additional qualitative research would provide a deeper understanding of the attributes of enablement in the primary health care setting.